Assessing Policy Effectiveness in Taxpayer Compliance: A Case Study from KPP Pratama Tangerang Timur - Sarah, Adhariani; Abbas, Yulianti (E-Jurnal Akuntansi, 2024)
The purpose of this study is to explore the application of taxpayer compliance supervision policies as outlined in SE-05/PJ/2022 at KPP Pratama Tangerang Timur. Utilizing qualitative case studies, this research incorporates data collected through in-depth interviews with compliance supervision practitioners and document analysis. The research framework, based on William Dunn's evaluation model, seeks to comprehensively assess the effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness of the policy. The findings suggest that the implementation of the SE-05/PJ/2022 supervision policy generally adheres to Dunn's evaluative criteria, although several challenges persist. This study provides an empirical reflection of the actual conditions experienced by supervisory officers in their operational roles. The outcomes of this research may serve as a foundational reference for the further development of taxpayer compliance supervision policies. Keywords: Tax Supervision ; Taxpayer Compliance